(untitled) (Journal of Medical & Health Sciences Review, 2025)
Globally more than one billion people have been estimated to be obese (BMI >30 kg/m²). In Pakistan near about 23% adult males are obese. Objective:This study aimed to evaluate the weight-reducing potential of Emblica officinalis extract(EE) in obese, physically active men through a triple-blind ,randomized and placebo-controlled clinical trial. Methods: After approval by IRB RLKU Medical College, a triple-blind, randomized, placebo-controlled, multicentered clinical trial was conducted in Lahore urban community for a period of 12 weeks from June 2025 to August 2025, recruiting 60 obese adult males .These patients were randomly assigned to either the Experimental Group receiving EE or the Control Group (placebo group) in 1 to 1 ratio. Anthropometric and clinical measurement were carried out before and at the end of study. for a period of 12 weeks. Primary outcome was reduction in weight. Results:Compared to the placebo group, participants receiving EE demonstrated a statistically significant reduction in body weight, BMI, and WHR (p < 0.05). No significant changes were observed in other parameters. Importantly, no adverse effects were reported throughout the study duration. Conclusion:These findings suggest that daily supplementation with Emblica officinalis extract, in combination with moderate physical activity may offer a safe and effective phytotherapeutic strategy for managing obesity in adult males.